The estimation problems of the fire hazard for vertically oriented building products/Vertikaliai orientuotų statybinių gaminių gaisrinio pavojingumo įvertinimo problemos - Nyderis, Albertas (Journal of Civil Engineering and Management, 1999)
The Directive of new approach 89/106/EEC, which was prepared by Directorate General of the European Commission (DG III), defines the guidelines for development of fire protection in building construction. Six main directions for development of fire protection are defined in this Directive as well. Solid materials are most numerous among building products. Therefore a brief analysis of combustion process of these materials is presented in this article. F.Williams developed the theoretical principles of combustion. Phase transitions in the zone of combustion are analyzed in the theory. Formulas 1–4 describe this process. The process of combustion of solid materials is heterogeneous; therefore the model of pyrolysis is presented by 5 formulas. An intricate energy exchange takes place in real fires. The heat is being transferred in different ways. The most acceptable description of heat transfer is by means of radiation. Description of this process is presented in formulas 6–7. The heat transfer by means of radiation can be modelled and used for environment testing. The combustibility of building products can be examined by means of reaction of fire tests. In recent years tests for different building products were carried out according to ISO 5657 test methodology in the Fire Research Centre. Test results indicate that the time to sustained surface ignition for building products is inversely proportional to heat flux. This logarithmic dependence is presented in 8 formulas. Establishment of parameters of this logarithmic flow for different building products can prove this. This work was carried out during the process of verification of this hypothesis. Analysis of fire testing practice of vertically oriented building products in different countries shows that harmonized fire test methods for these products do not exist. Most of these test methods are based on presumption that the flame spread is possible only inside the building not considering the behaviour of facade in fire. The main idea of fire test method for element of vertically oriented building construction together with the principal scheme of test equipment are presented in the article as well. Further development of this idea leads to five questions, which should be answered to solve the problem. After the completion of this task and analysis of test results, all the information is to be submitted for further consideration.Article in Lithuanian.First Published Online: 26 Jul 2012